Pengaruh Penetapan Harga dan Promosi terhadap Penjualan UMKM Zenira Official (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study examines the impact of pricing strategies and promotions on sales at Zenira Official, an SME specializing in sandal sales through online platforms. With increasing competition in the e-commerce industry, competitive pricing and attractive promotions play a crucial role in attracting consumers and boosting sales volume. This research employs a qualitative approach using triangulation methods, where data is collected through interviews with Zenira Official's owner, marketing team, and finance department. The findings indicate that competitive pricing enhances customer interest, particularly when aligned with product quality. In conclusion, the right combination of pricing and promotional strategies can significantly improve sales and ensure business sustainability in the digital marketplace.